Adherent leukoma with iris prolapse and cataract in old farmer patient : a case report: Poster Presentation - Case Report - General practitioner - Lulu Hasna Ulfadila; Hilman Hitam (Majalah Oftalmologi Indonesia, 2023)
Introduction : Adherent leukoma is a condition of the formation of white scars with the involvement of iris incarceration on the cornea, scar which has fibrous tissue adherent to its deeper surface. Case Illustration : a 70 year old grandfather with complaints of blurry right and left eyes, especially in the left eye there are white spots that increasingly interfere with discomfort vision in 5 months ago. The patient works as a rice farmer every day and is likely due to frequent trauma from being exposed to rice seeds since he was young. There is no history of disease and he likely to used insto eye drops. General physical examination is normal. VODS 6/15. IOP OD 11 and OS 7. There is adherens leukoma at 11 o'clock and iris prolapse and there are cataracts as well as the right and left eyes which are still thin. fundoscopy within normal limits. Discussion : Corneal opacity such as adherent leukoma generally results from incidental or iatrogenic trauma. In this case, the patient was traumatized showed post-traumatic cases to be the most common cause of corneal opacity (47.2%), followed by post-ulceration cases (37.7%), glaucoma (7.5%), and other unknown causes (4%). A few rare cases of non-traumatic bilateral adherent leukoma have been described to occur in association with protein energy malnutrition, vitamin A deficiency, herpetic infections and measles. Corneal tattoos and corneal transplantation have been used in treating corneal opacities with varying results. Conclusion : White corneal scar on leucoma represents fibrosis secondary to a previous corneal insult, most frequently trauma or infection.